This is an alternative site for discovering Elm packages. You may be looking for the official Elm package site instead.
README

Shrink

Library containing a collection of basic shrinking strategies and helper functions to help you construct shrinking strategies.

Shrinking Basics

type alias Shrinker a = a -> LazyList a

The shrinker type. A shrinker is a function that takes a value and returns a list of values that are in some sense "smaller" than the given value. If there are no such values conceptually, then the shrinker should just return the empty list.

shrink : (a -> Bool) -> Shrinker a -> a -> a

Perform shrinking. Takes a predicate that returns True if you want shrinking to continue (e.g. the test failed). Also takes a shrinker and a value to shrink. It returns the shrunken value, or the input value if no shrunken values that satisfy the predicate are found.

Shrinkers

noShrink : Shrinker a

Perform no shrinking. Equivalent to the empty lazy list.

unit : Shrinker ()

Shrink the empty tuple. Equivalent to noShrink.

bool : Shrinker Bool

Shrinker of bools.

order : Shrinker Order

Shrinker of Order values.

int : Shrinker Int

Shrinker of integers.

atLeastInt : Int -> Shrinker Int

Construct a shrinker of ints which considers the given int to be most minimal.

float : Shrinker Float

Shrinker of floats.

atLeastFloat : Float -> Shrinker Float

Construct a shrinker of floats which considers the given float to be most minimal.

char : Shrinker Char

Shrinker of chars.

atLeastChar : Char -> Shrinker Char

Construct a shrinker of chars which considers the given char to be most minimal.

character : Shrinker Char

Shrinker of chars which considers the empty space as the most minimal char and omits the control key codes.

Equivalent to:

atLeastChar (Char.fromCode 32)
string : Shrinker String

Shrinker of strings. Considers the empty string to be the most minimal string and the space to be the most minimal char.

Equivalent to:

convert String.fromList String.toList (list character)
maybe : Shrinker a -> Shrinker (Maybe a)

Maybe shrinker constructor. Takes a shrinker of values and returns a shrinker of Maybes.

result : Shrinker error -> Shrinker value -> Shrinker (Result error value)

Result shrinker constructor. Takes a shrinker of errors and a shrinker of values and returns a shrinker of Results.

lazylist : Shrinker a -> Shrinker (LazyList a)

Lazy List shrinker constructor. Takes a shrinker of values and returns a shrinker of Lazy Lists. The lazy list being shrunk must be finite. (I mean really, how do you shrink infinity?)

list : Shrinker a -> Shrinker (List a)

List shrinker constructor. Takes a shrinker of values and returns a shrinker of Lists.

array : Shrinker a -> Shrinker (Array a)

Array shrinker constructor. Takes a shrinker of values and returns a shrinker of Arrays.

tuple : ( Shrinker a, Shrinker b ) -> Shrinker ( a, b )

2-Tuple shrinker constructor. Takes a tuple of shrinkers and returns a shrinker of tuples.

tuple3 : ( Shrinker a, Shrinker b, Shrinker c ) -> Shrinker ( a, b, c )

3-Tuple shrinker constructor. Takes a tuple of shrinkers and returns a shrinker of tuples.

tuple4 : ( Shrinker a, Shrinker b, Shrinker c, Shrinker d ) -> Shrinker ( a, b, c, d )

4-Tuple shrinker constructor. Takes a tuple of shrinkers and returns a shrinker of tuples.

tuple5 : ( Shrinker a, Shrinker b, Shrinker c, Shrinker d, Shrinker e ) -> Shrinker ( a, b, c, d, e )

5-Tuple shrinker constructor. Takes a tuple of shrinkers and returns a shrinker of tuples.

Functions on Shrinkers

convert : (a -> b) -> (b -> a) -> Shrinker a -> Shrinker b

Convert a Shrinker of a's into a Shrinker of b's using two inverse functions.

If you use this function as follows:

shrinkerB = f g shrinkerA

Make sure that

`f(g(x)) == x` for all x

Or else this process will generate garbage.

keepIf : (a -> Bool) -> Shrinker a -> Shrinker a

Filter out the results of a shrinker. The resulting shrinker will only produce shrinks which satisfy the given predicate.

dropIf : (a -> Bool) -> Shrinker a -> Shrinker a

Filter out the results of a shrinker. The resulting shrinker will only throw away shrinks which satisfy the given predicate.

merge : Shrinker a -> Shrinker a -> Shrinker a

Merge two shrinkers. Generates all the values in the first shrinker, and then all the non-duplicated values in the second shrinker.

map : (a -> b) -> LazyList a -> LazyList b

Re-export of Lazy.List.map This is useful in order to compose shrinkers, especially when used in conjunction with andMap. For example:

type alias Vector =
  { x : Float
  , y : Float
  , z : Float
  }

vector : Shrinker Vector
vector {x,y,z} =
  Vector
    `map`    float x
    `andMap` float y
    `andMap` float z
andMap : LazyList a -> LazyList (a -> b) -> LazyList b

Apply a lazy list of functions on a lazy list of values.

The argument order is so that it is easy to use in |> chains.

module Shrink exposing (Shrinker, shrink, noShrink, unit, bool, order, int, atLeastInt, float, atLeastFloat, char, atLeastChar, character, string, maybe, result, list, lazylist, array, tuple, tuple3, tuple4, tuple5, convert, keepIf, dropIf, merge, map, andMap)

{-| Library containing a collection of basic shrinking strategies and
helper functions to help you construct shrinking strategies.

# Shrinking Basics
@docs Shrinker, shrink

# Shrinkers
@docs noShrink, unit, bool, order, int, atLeastInt, float, atLeastFloat, char, atLeastChar, character, string, maybe, result, lazylist, list, array, tuple, tuple3, tuple4, tuple5

# Functions on Shrinkers
@docs convert, keepIf, dropIf, merge, map, andMap

-}

import Lazy.List exposing (LazyList, (:::), (+++), empty)
import Lazy exposing (Lazy, force, lazy)
import List
import Array exposing (Array)
import Char
import String


{-| The shrinker type.
A shrinker is a function that takes a value and returns a list of values that
are in some sense "smaller" than the given value. If there are no such values
conceptually, then the shrinker should just return the empty list.
-}
type alias Shrinker a =
    a -> LazyList a


{-| Perform shrinking. Takes a predicate that returns `True` if you want
shrinking to continue (e.g. the test failed). Also takes a shrinker and a value
to shrink. It returns the shrunken value, or the input value if no shrunken
values that satisfy the predicate are found.
-}
shrink : (a -> Bool) -> Shrinker a -> a -> a
shrink keepShrinking shrinker originalVal =
    let
        helper lazyList val =
            case force lazyList of
                Lazy.List.Nil ->
                    val

                Lazy.List.Cons head tail ->
                    if keepShrinking head then
                        helper (shrinker head) head
                    else
                        helper tail val
    in
        helper (shrinker originalVal) originalVal


{-| Perform no shrinking. Equivalent to the empty lazy list.
-}
noShrink : Shrinker a
noShrink _ =
    empty


{-| Shrink the empty tuple. Equivalent to `noShrink`.
-}
unit : Shrinker ()
unit =
    noShrink


{-| Shrinker of bools.
-}
bool : Shrinker Bool
bool b =
    case b of
        True ->
            False ::: empty

        False ->
            empty


{-| Shrinker of `Order` values.
-}
order : Shrinker Order
order o =
    case o of
        GT ->
            EQ ::: LT ::: empty

        LT ->
            EQ ::: empty

        EQ ->
            empty


{-| Shrinker of integers.
-}
int : Shrinker Int
int n =
    if n < 0 then
        -n ::: Lazy.List.map ((*) -1) (seriesInt 0 -n)
    else
        seriesInt 0 n


{-| Construct a shrinker of ints which considers the given int to
be most minimal.
-}
atLeastInt : Int -> Shrinker Int
atLeastInt min n =
    if n < 0 && n >= min then
        -n ::: Lazy.List.map ((*) -1) (seriesInt 0 -n)
    else
        seriesInt (max 0 min) n


{-| Shrinker of floats.
-}
float : Shrinker Float
float n =
    if n < 0 then
        -n ::: Lazy.List.map ((*) -1) (seriesFloat 0 -n)
    else
        seriesFloat 0 n


{-| Construct a shrinker of floats which considers the given float to
be most minimal.
-}
atLeastFloat : Float -> Shrinker Float
atLeastFloat min n =
    if n < 0 && n >= min then
        -n ::: Lazy.List.map ((*) -1) (seriesFloat 0 -n)
    else
        seriesFloat (max 0 min) n


{-| Shrinker of chars.
-}
char : Shrinker Char
char =
    convert Char.fromCode Char.toCode int


{-| Construct a shrinker of chars which considers the given char to
be most minimal.
-}
atLeastChar : Char -> Shrinker Char
atLeastChar char =
    convert Char.fromCode Char.toCode (atLeastInt (Char.toCode char))


{-| Shrinker of chars which considers the empty space as the most
minimal char and omits the control key codes.

Equivalent to:

    atLeastChar (Char.fromCode 32)
-}
character : Shrinker Char
character =
    atLeastChar (Char.fromCode 32)


{-| Shrinker of strings. Considers the empty string to be the most
minimal string and the space to be the most minimal char.

Equivalent to:

    convert String.fromList String.toList (list character)
-}
string : Shrinker String
string =
    convert String.fromList String.toList (list character)


{-| Maybe shrinker constructor.
Takes a shrinker of values and returns a shrinker of Maybes.
-}
maybe : Shrinker a -> Shrinker (Maybe a)
maybe shrink m =
    case m of
        Just a ->
            Nothing ::: Lazy.List.map Just (shrink a)

        Nothing ->
            empty


{-| Result shrinker constructor. Takes a shrinker of errors and a shrinker of
values and returns a shrinker of Results.
-}
result : Shrinker error -> Shrinker value -> Shrinker (Result error value)
result shrinkError shrinkValue r =
    case r of
        Ok value ->
            Lazy.List.map Ok (shrinkValue value)

        Err error ->
            Lazy.List.map Err (shrinkError error)


{-| Lazy List shrinker constructor. Takes a shrinker of values and returns a
shrinker of Lazy Lists. The lazy list being shrunk must be finite. (I mean
really, how do you shrink infinity?)
-}
lazylist : Shrinker a -> Shrinker (LazyList a)
lazylist shrink l =
    lazy <|
        \() ->
            let
                n : Int
                n =
                    Lazy.List.length l

                shrinkOne : LazyList a -> LazyList (LazyList a)
                shrinkOne l =
                    lazy <|
                        \() ->
                            case force l of
                                Lazy.List.Nil ->
                                    force empty

                                Lazy.List.Cons x xs ->
                                    force
                                        (Lazy.List.map (flip (:::) xs) (shrink x)
                                            +++ Lazy.List.map ((:::) x) (shrinkOne xs)
                                        )

                removes : Int -> Int -> Shrinker (LazyList a)
                removes k n l =
                    lazy <|
                        \() ->
                            if k > n then
                                force empty
                            else if Lazy.List.isEmpty l then
                                force (empty ::: empty)
                            else
                                let
                                    first =
                                        Lazy.List.take k l

                                    rest =
                                        Lazy.List.drop k l
                                in
                                    force <|
                                        rest
                                            ::: Lazy.List.map ((+++) first) (removes k (n - k) rest)
            in
                force <|
                    Lazy.List.andThen (\k -> removes k n l)
                        (Lazy.List.takeWhile (\x -> x > 0) (Lazy.List.iterate (\n -> n // 2) n))
                        +++ shrinkOne l


{-| List shrinker constructor.
Takes a shrinker of values and returns a shrinker of Lists.
-}
list : Shrinker a -> Shrinker (List a)
list shrink =
    convert Lazy.List.toList Lazy.List.fromList (lazylist shrink)


{-| Array shrinker constructor.
Takes a shrinker of values and returns a shrinker of Arrays.
-}
array : Shrinker a -> Shrinker (Array a)
array shrink =
    convert Lazy.List.toArray Lazy.List.fromArray (lazylist shrink)


{-| 2-Tuple shrinker constructor.
Takes a tuple of shrinkers and returns a shrinker of tuples.
-}
tuple : ( Shrinker a, Shrinker b ) -> Shrinker ( a, b )
tuple ( shrinkA, shrinkB ) ( a, b ) =
    Lazy.List.map ((,) a) (shrinkB b)
        +++ Lazy.List.map (flip (,) b) (shrinkA a)
        +++ Lazy.List.map2 (,) (shrinkA a) (shrinkB b)


{-| 3-Tuple shrinker constructor.
Takes a tuple of shrinkers and returns a shrinker of tuples.
-}
tuple3 : ( Shrinker a, Shrinker b, Shrinker c ) -> Shrinker ( a, b, c )
tuple3 ( shrinkA, shrinkB, shrinkC ) ( a, b, c ) =
    Lazy.List.map (\c -> ( a, b, c )) (shrinkC c)
        +++ Lazy.List.map (\b -> ( a, b, c )) (shrinkB b)
        +++ Lazy.List.map (\a -> ( a, b, c )) (shrinkA a)
        +++ Lazy.List.map2 (\b c -> ( a, b, c )) (shrinkB b) (shrinkC c)
        +++ Lazy.List.map2 (\a c -> ( a, b, c )) (shrinkA a) (shrinkC c)
        +++ Lazy.List.map2 (\a b -> ( a, b, c )) (shrinkA a) (shrinkB b)
        +++ Lazy.List.map3 (,,) (shrinkA a) (shrinkB b) (shrinkC c)


{-| 4-Tuple shrinker constructor.
Takes a tuple of shrinkers and returns a shrinker of tuples.
-}
tuple4 : ( Shrinker a, Shrinker b, Shrinker c, Shrinker d ) -> Shrinker ( a, b, c, d )
tuple4 ( shrinkA, shrinkB, shrinkC, shrinkD ) ( a, b, c, d ) =
    Lazy.List.map (\d -> ( a, b, c, d )) (shrinkD d)
        +++ Lazy.List.map (\c -> ( a, b, c, d )) (shrinkC c)
        +++ Lazy.List.map (\b -> ( a, b, c, d )) (shrinkB b)
        +++ Lazy.List.map (\a -> ( a, b, c, d )) (shrinkA a)
        +++ Lazy.List.map2 (\c d -> ( a, b, c, d )) (shrinkC c) (shrinkD d)
        +++ Lazy.List.map2 (\b d -> ( a, b, c, d )) (shrinkB b) (shrinkD d)
        +++ Lazy.List.map2 (\a d -> ( a, b, c, d )) (shrinkA a) (shrinkD d)
        +++ Lazy.List.map2 (\b c -> ( a, b, c, d )) (shrinkB b) (shrinkC c)
        +++ Lazy.List.map2 (\a c -> ( a, b, c, d )) (shrinkA a) (shrinkC c)
        +++ Lazy.List.map2 (\a b -> ( a, b, c, d )) (shrinkA a) (shrinkB b)
        +++ Lazy.List.map3 (\b c d -> ( a, b, c, d )) (shrinkB b) (shrinkC c) (shrinkD d)
        +++ Lazy.List.map3 (\a c d -> ( a, b, c, d )) (shrinkA a) (shrinkC c) (shrinkD d)
        +++ Lazy.List.map3 (\a b d -> ( a, b, c, d )) (shrinkA a) (shrinkB b) (shrinkD d)
        +++ Lazy.List.map3 (\a b c -> ( a, b, c, d )) (shrinkA a) (shrinkB b) (shrinkC c)
        +++ Lazy.List.map4 (,,,) (shrinkA a) (shrinkB b) (shrinkC c) (shrinkD d)


{-| 5-Tuple shrinker constructor.
Takes a tuple of shrinkers and returns a shrinker of tuples.
-}
tuple5 : ( Shrinker a, Shrinker b, Shrinker c, Shrinker d, Shrinker e ) -> Shrinker ( a, b, c, d, e )
tuple5 ( shrinkA, shrinkB, shrinkC, shrinkD, shrinkE ) ( a, b, c, d, e ) =
    Lazy.List.map (\e -> ( a, b, c, d, e )) (shrinkE e)
        +++ Lazy.List.map (\d -> ( a, b, c, d, e )) (shrinkD d)
        +++ Lazy.List.map (\c -> ( a, b, c, d, e )) (shrinkC c)
        +++ Lazy.List.map (\b -> ( a, b, c, d, e )) (shrinkB b)
        +++ Lazy.List.map (\a -> ( a, b, c, d, e )) (shrinkA a)
        +++ Lazy.List.map2 (\d e -> ( a, b, c, d, e )) (shrinkD d) (shrinkE e)
        +++ Lazy.List.map2 (\c e -> ( a, b, c, d, e )) (shrinkC c) (shrinkE e)
        +++ Lazy.List.map2 (\b e -> ( a, b, c, d, e )) (shrinkB b) (shrinkE e)
        +++ Lazy.List.map2 (\a e -> ( a, b, c, d, e )) (shrinkA a) (shrinkE e)
        +++ Lazy.List.map2 (\c d -> ( a, b, c, d, e )) (shrinkC c) (shrinkD d)
        +++ Lazy.List.map2 (\b d -> ( a, b, c, d, e )) (shrinkB b) (shrinkD d)
        +++ Lazy.List.map2 (\a d -> ( a, b, c, d, e )) (shrinkA a) (shrinkD d)
        +++ Lazy.List.map2 (\b c -> ( a, b, c, d, e )) (shrinkB b) (shrinkC c)
        +++ Lazy.List.map2 (\a c -> ( a, b, c, d, e )) (shrinkA a) (shrinkC c)
        +++ Lazy.List.map2 (\a b -> ( a, b, c, d, e )) (shrinkA a) (shrinkB b)
        +++ Lazy.List.map3 (\a b c -> ( a, b, c, d, e )) (shrinkA a) (shrinkB b) (shrinkC c)
        +++ Lazy.List.map3 (\a b d -> ( a, b, c, d, e )) (shrinkA a) (shrinkB b) (shrinkD d)
        +++ Lazy.List.map3 (\a c d -> ( a, b, c, d, e )) (shrinkA a) (shrinkC c) (shrinkD d)
        +++ Lazy.List.map3 (\b c d -> ( a, b, c, d, e )) (shrinkB b) (shrinkC c) (shrinkD d)
        +++ Lazy.List.map3 (\a b e -> ( a, b, c, d, e )) (shrinkA a) (shrinkB b) (shrinkE e)
        +++ Lazy.List.map3 (\a c e -> ( a, b, c, d, e )) (shrinkA a) (shrinkC c) (shrinkE e)
        +++ Lazy.List.map3 (\b c e -> ( a, b, c, d, e )) (shrinkB b) (shrinkC c) (shrinkE e)
        +++ Lazy.List.map3 (\a d e -> ( a, b, c, d, e )) (shrinkA a) (shrinkD d) (shrinkE e)
        +++ Lazy.List.map3 (\b d e -> ( a, b, c, d, e )) (shrinkB b) (shrinkD d) (shrinkE e)
        +++ Lazy.List.map3 (\c d e -> ( a, b, c, d, e )) (shrinkC c) (shrinkD d) (shrinkE e)
        +++ Lazy.List.map4 (\b c d e -> ( a, b, c, d, e )) (shrinkB b) (shrinkC c) (shrinkD d) (shrinkE e)
        +++ Lazy.List.map4 (\a c d e -> ( a, b, c, d, e )) (shrinkA a) (shrinkC c) (shrinkD d) (shrinkE e)
        +++ Lazy.List.map4 (\a b d e -> ( a, b, c, d, e )) (shrinkA a) (shrinkB b) (shrinkD d) (shrinkE e)
        +++ Lazy.List.map4 (\a b c d -> ( a, b, c, d, e )) (shrinkA a) (shrinkB b) (shrinkC c) (shrinkD d)
        +++ Lazy.List.map5 (,,,,) (shrinkA a) (shrinkB b) (shrinkC c) (shrinkD d) (shrinkE e)



----------------------
-- HELPER FUNCTIONS --
----------------------


{-| Convert a Shrinker of a's into a Shrinker of b's using two inverse functions.

If you use this function as follows:

    shrinkerB = f g shrinkerA

Make sure that

    `f(g(x)) == x` for all x

Or else this process will generate garbage.
-}
convert : (a -> b) -> (b -> a) -> Shrinker a -> Shrinker b
convert f g shrink b =
    Lazy.List.map f (shrink (g b))


{-| Filter out the results of a shrinker. The resulting shrinker
will only produce shrinks which satisfy the given predicate.
-}
keepIf : (a -> Bool) -> Shrinker a -> Shrinker a
keepIf predicate shrink a =
    Lazy.List.keepIf predicate (shrink a)


{-| Filter out the results of a shrinker. The resulting shrinker
will only throw away shrinks which satisfy the given predicate.
-}
dropIf : (a -> Bool) -> Shrinker a -> Shrinker a
dropIf predicate =
    keepIf (not << predicate)


{-| Merge two shrinkers. Generates all the values in the first
shrinker, and then all the non-duplicated values in the second
shrinker.
-}
merge : Shrinker a -> Shrinker a -> Shrinker a
merge shrink1 shrink2 a =
    Lazy.List.unique (shrink1 a +++ shrink2 a)


{-| Re-export of `Lazy.List.map`
This is useful in order to compose shrinkers, especially when used in
conjunction with `andMap`. For example:

    type alias Vector =
      { x : Float
      , y : Float
      , z : Float
      }

    vector : Shrinker Vector
    vector {x,y,z} =
      Vector
        `map`    float x
        `andMap` float y
        `andMap` float z
-}
map : (a -> b) -> LazyList a -> LazyList b
map =
    Lazy.List.map


{-| Apply a lazy list of functions on a lazy list of values.

The argument order is so that it is easy to use in `|>` chains.
-}
andMap : LazyList a -> LazyList (a -> b) -> LazyList b
andMap =
    Lazy.List.andMap



-----------------------
-- PRIVATE FUNCTIONS --
-----------------------


seriesInt : Int -> Int -> LazyList Int
seriesInt low high =
    if low >= high then
        empty
    else if low == high - 1 then
        low ::: empty
    else
        let
            low_ =
                low + ((high - low) // 2)
        in
            low ::: seriesInt low_ high


seriesFloat : Float -> Float -> LazyList Float
seriesFloat low high =
    if low >= high - 0.0001 then
        if high /= 0.000001 then
            Lazy.List.singleton (low + 0.000001)
        else
            empty
    else
        let
            low_ =
                low + ((high - low) / 2)
        in
            low ::: seriesFloat low_ high